Systemic juvenile idiopathic arthritis: The Great Ormond Street Hospital experience (2005–2021) - Foley, C. M.; McKenna, D.; Gallagher, K.; McLellan, K.; Alkhdher, H.; Lacassagne, S.; Moraitis, E.; Papadopoulou, C.; Pilkington, C.; Al Obaidi, M.; Eleftheriou, D.; Brogan, P. (Frontiers in Pediatrics, 2023)
sJIA is a complex, systemic-inflammatory disorder, driven by both innate and adaptive-immunity.Improved understanding of sJIA-pathophysiology has led to recent therapeutic-advances including a growing evidence-base for the earlier use of IL-1 or IL-6-blockade as first-line treatment.We conducted a retrospective case-notes review of patients diagnosed with sJIA over a 16-year period (October 2005-October 2021) at GOSH.We describe the clinical-presentation, therapeutic-interventions, complications, and remission-rates at different time-points over the disease-course.We examined our data, which spanned a period of changing therapeutic-landscape, to try and identify potential therapeutic-signals in patients who received biologic-treatment early in the disease-course compared to those who did not.A total of 76-children (female n=40, 53%) were diagnosed with sJIA, median-age 4.5 years(range 0.6-14.1); 36%(27/76) presented with suspected or confirmed MAS.A biologic disease-modifying anti-rheumatic drug (bDMARD) alone was commenced as first-line treatment in 28%(n=21/76) of the cohort; however, at last review, 84%(n=64/76) had received treatment with a bDMARD. Clinically-inactive-disease (CID) was achieved by 88%(n=67/76)of the cohort at last review, however only 32%(24/76) achieved treatment-free CID.At 1-year follow-up, CID was achieved in a significantly greater proportion of children who received treatment with a bDMARD within 3-months of diagnosis compared to those who did not (90% versus 53%, p=0.002).Based on an ever-increasing evidence-base for the earlier use of bDMARD in sJIA and our experience of the largest UK single-centre case-series described to date, we now propose a new therapeutic-pathway for children diagnosed with sJIA in the UK based on early use of bDMARD.Reappraisal of the current NHS-commissioning pathway for sJIA is now urgently required.